Knowing me, knowing you: perspectives on awareness in autism. Issue 4 (21st December 2015) - Yuill, Nicola; Parsons, Sarah; Good, Judith; Brosnan, Mark
Abstract : Purpose: – The purpose of this paper is to raise important questions from the different perspectives on autism research that arose from a seminar on autism and technology, held as part of an ESRC-funded series on innovative technologies for autism. Design/methodology/approach: – The paper focuses on the roles of technology in understanding questions about different perspectives on autism: how do people on the spectrum see neurotypicals (people without autism) and vice versa?; how do the authors use eye gaze differently from each other?; how might technology influence what is looked at and how the authors measure this?; what differences might there be in how people use imitation of others?; and finally, how should the authors study and treat any differences? Findings: – The authors synthesise common themes from invited talks and responses. The audience discussions highlighted the ways in which the authors take account of human variation, how the authors can understand the perspective of another, particularly across third-person and second-person approaches in research, and how researchers and stakeholders engage with each other. Originality/value: – The authors argue that the question of perspectives is important for considering how people with autism and neurotypical people interact in everyday contexts, and how researchers frame their research questions and methods. The authors propose that stakeholders and researchers can fruitfully engage directly in discussions of research, in ways that benefit both research and practice.